O movimentar-se no processo de humanização da criança : diálogos com Jean-Jacques Rousseau - Oliveira, Rosemary Coelho de (2011)
This research focuses on the theme of education of children and within this spectrum, investigates, in work or education of Emile Jean-Jacques Rousseau, the place that occupies the move in the process of inclusion of children in the human world. The article draws as theoretical reflections on Karl Marx about the constitution of the social. Jogging is initially seen by Rousseau as a natural necessity. The Genevan philosopher recognizes the movement as the first mode of the child to know and be recognized worldwide. For Rousseau, the importance of moving with freedom is expressed in the fact that it is intrinsically relate to human existence. For him, and confused with the existence, in the course of child development, the movement wins usefulness through crafts and exercises that help strengthen the temperament and health. Rousseau asserts that the child should experience those bodily practices that are culturally performed by adults, even if some adaptations are necessary. In the center of the educational process, is therefore the child. The position of Rousseau about the place that occupies the move in the process of social constitution of the human being is based on a very complex framework in which "live" innovations and problematic aspects. The determination of a natural essence for human beings is affirmed at the same time that inequality is seen as a product of human action. In Rousseau, our natural condition refers to the traits of kindness and equality that nature gives us. However, the construction of the social world can respect this natural vocation or may antagonize her. Therefore, these natural attributes are subject to change. There is, in Rousseau, a historical dynamism that comes to live with that essentialist ontology natural. The natural essentialism proposed by Rousseau offers subsidies understanding that human development occurs in stages that are also naturally put and have universal validity. At the core of this framework is the postulation that human development is a natural progression of steps ordered, fixed and universal. The social appears as one that can provide a good development as regards the natural route or can stand as an impediment to update the natural essence of the human being. Rousseau understands the practical activity of the child, know your sensitive is the base which is human reason. This understanding calls into question certain aspects of the philosophical tradition of devaluation of the body, manual labor and bodily practices in general. However, by emphasizing the sensitive activity in the early stages, sometimes Rousseau purges the intellectual work of child development. This subject is a delicate one, considering that, at the very moment that characterizes childhood as sleep of reason and still maintains the dichotomy and hierarchy between soul and body, he mentions the existence in childhood, a complex reason, a reason sensitive. When it does so, Rousseau opens the possibility of capturing the intertwining of reason and sensibility in becoming human, in the case of children, their experiences already sensitive imply the development of consciousness, albeit initial form of contact right with the world. Finally, the distinction between the nature of education, education and education of men the objects descends into an "object fetishism" which turns out to counter a defense of Rousseau constant throughout his book: the importance of mediation in the adult educational process. As a classic of educational theory, Rousseau and inspires new questions need to be understood in a complexity not without inconsistencies and innovations.